Structural and mechanistic basis of penicillin-binding protein inhibition by lactivicins. - Macheboeuf, P; Fischer, D; Brown, T; Zervosen, A; Luxen, A; Joris, B; Dessen, A; Schofield, C (2007)
Beta-lactam antibiotics, including penicillins and cephalosporins, inhibit penicillin-binding proteins (PBPs), which are essential for bacterial cell wall biogenesis. Pathogenic bacteria have evolved efficient antibiotic resistance mechanisms that, in Gram-positive bacteria, include mutations to PBPs that enable them to avoid beta-lactam inhibition. Lactivicin (LTV; 1) contains separate cycloserine and gamma-lactone rings and is the only known natural PBP inhibitor that does not contain a beta-lactam. Here we show that LTV and a more potent analog, phenoxyacetyl-LTV (PLTV; 2), are active against clinically isolated, penicillin-resistant Streptococcus pneumoniae strains. Crystallographic analyses of S. pneumoniae PBP1b reveal that LTV and PLTV inhibition involves opening of both monocyclic cycloserine and gamma-lactone rings. In PBP1b complexes, the ring-derived atoms from LTV and PLTV show a notable structural convergence with those derived from a complexed cephalosporin (cefotaxime; 3). The structures imply that derivatives of LTV will be useful in the search for new antibiotics with activity against beta-lactam-resistant bacteria.